Deconstructing The Scientific Landscape In Sustainable Business: A Bibliometric Analysis Systematic Literature Review (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Research on sustainable business has experienced exponential growth in the last decade, reflecting the global urgency for more socially and ecologically responsible business practices. This study adopts a bibliometric and Systematic Literature Review (SLR) approach to map the intellectual landscape, identify research trends and highlight the most influential academic contributions in the discipline. By analysing more than 17,000 articles from the Scopus database from 2005 to 2025, the study reveals publication patterns, networks of scholarly collaboration, and conceptual dynamics that shape the discourse on corporate sustainability strategies and circular economy. The analysis indicates that stakeholder-based approaches and the integration of sustainability in the supply chain are the main pillars of building sustainable business models.
Keywords: Sustainable Business, Bibliometric Analysis, Systematic Literature Review, Corporate Sustainability Strategy, Circular Economy